2020
DOI: 10.1080/23802359.2020.1827061
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of Chionoecetes japonicus (Crustacea: Decapoda: Majoidea)

Abstract: The complete mitochondrial genome of Chionoecetes japonicus was sequenced using a specimen collected offshore in the East Sea. The genome includes 13 protein-coding genes (PCGs), 22 transfer RNA (tRNA) genes, two ribosomal RNA (rRNA) genes, and a control region (D-loop), with a total length of 16,060 bp. The overall nucleotide composition was 34.91% A, 17.29% C, 10.93% G, and 36.87% T, with 71.78% A þ T. In the phylogenetic tree was constructed using maximum-likelihood and Bayesian inference analyses, C. japon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…The molecular phylogeny suggested that S. compressipes clustered with Maguimithrax spinosissimus, a representative of the Mithracidae (Figure 1). The molecular phylogenetic relationship between families in the superfamily Majoidea presented in this study was consistent to previous studies (Hultgren and Stachowicz 2008;Jeong et al 2020;Kim et al 2020).…”
supporting
confidence: 92%
“…The molecular phylogeny suggested that S. compressipes clustered with Maguimithrax spinosissimus, a representative of the Mithracidae (Figure 1). The molecular phylogenetic relationship between families in the superfamily Majoidea presented in this study was consistent to previous studies (Hultgren and Stachowicz 2008;Jeong et al 2020;Kim et al 2020).…”
supporting
confidence: 92%